The improvement of multi-contaminated sandy loam soil chemical and biological properties by the biochar, wood ash, and humic substances amendments. (October 2017) - Pukalchik, Maria; Mercl, Filip; Panova, Maria; Břendová, Kateřina; Terekhova, Vera A.; Tlustoš, Pavel
Abstract: Nowadays trace metal contamination of soils represents an important environmental hazard. Nevertheless, the use of some secondary waste products as amendments may restore the common soil functions. This paper focuses on the chemical and biological influence of wood biochar (BC), wood ash (WA) and humic substances (HS), alone and in the mixtures, on a heavily multi-contaminated sandy loam soil. The soil was amended by above-mentioned materials to follow a pH-increasing design (pHCa from 6.0 to 6.5, 7.0 and 7.5); soil samples were analyzed after 3, 30, and 60 days using a set of variables, namely the plant-available trace element concentrations (Cu, Cd, and Zn), microbial biomass carbon (Cmic), and microbial quotient (qCO2 ), as well as toxicity to Sinapis alba and Daphnia magna . Wood ash and WA + HS were the most efficient treatments to decrease mobile Cd and Zn concentrations in the soil, while HS, BC, and BC + HS combinations were the most effective in reducing the Cu mobility. The effect of BC and WA on the Cmic and qCO2 was mostly negative, whereas adding HS markedly increased Cmic and reduced qCO2 in soil. After amendment applications, the root elongation of mustard was significantly increased in HS and combined treatments (BC + HS, WA + HS). Additionally, BC + HS, WA + HS and WA 8.4% significantly decreased the toxicity of leachates to D. magna to the low-, or non-toxic levels. Our results suggest that the combination of amendments with HS can be a suitable remediation strategy for heavily contaminated soils. Graphical abstract: Highlights: WA and combinations of WA + HS reduced Zn and Cd plant-availability, while BC and BC + HS reduced Cu plant-availability. HS mitigated WA and BC soil toxicity. HS had a stimulating effect on soil Cmic biomass and positively influenced qCO2 . Abstract : Addition of low amount of humic substances, as a supplement to biochar or wood ash, can markedly enhance their remediation ability.